2010
DOI: 10.1111/j.1442-2050.2010.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

NK cell dysfunction with down-regulated CD16 and up-regulated CD56 molecules in patients with esophageal squamous cell carcinoma

Abstract: NK cells can be divided into two subsets, CD56(dim) and CD56(bright) NK cells, based on their expression of CD56 and CD16. In the present study, we analyzed NK cell dysfunction in patients with esophageal squamous cell carcinoma (ESCC), with a particular focus on the expression of CD16 and CD56 molecules. Expression of CD16 and CD56, and the distribution of CD56(dim) or CD56(bright) NK cells gated on CD56(+)CD3(-) NK cells were compared between ESCC patients (n= 40) and healthy donors (n= 38). Purified NK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…It has been already reported that the ADCC activities in advanced cancer patients were impaired due to several mechanisms, including NK cell dysfunction or immunosuppressive factors (8,23,24). As expected, we confirmed that the cetuximab-mediated and trastuzumab-mediated ADCCs in advanced disease were impaired in comparison to those in early disease or healthy individuals (Fig.…”
Section: Defucosylated Cetuximab-and Trastuzumab-mediated Adcc In Advsupporting
confidence: 77%
See 2 more Smart Citations
“…It has been already reported that the ADCC activities in advanced cancer patients were impaired due to several mechanisms, including NK cell dysfunction or immunosuppressive factors (8,23,24). As expected, we confirmed that the cetuximab-mediated and trastuzumab-mediated ADCCs in advanced disease were impaired in comparison to those in early disease or healthy individuals (Fig.…”
Section: Defucosylated Cetuximab-and Trastuzumab-mediated Adcc In Advsupporting
confidence: 77%
“…It is generally accepted that NK cells in cancer-bearing hosts are impaired by many mechanisms, including their reduced number, imbalances in their activating and inhibitory receptor, impaired activation signaling cascade as well as immunosuppressive cytokines (8,23,24). However, even in such a condition, the current study clearly indicated that the defucosylated mAbs can restore the impaired ADCC in advanced diseases.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…33,34 Similar changes and dysfunction were reported in NK cells isolated from patients with esophageal squamous cell carcinoma and non-small cell lung carcinoma, particularly in pleural effusion. 38,39 The downregulation of CD16 on NK cells has been shown to be driven by TGFβ and leads to conversion from cytotoxic to a more immunoregulatory phenotype similar to decidual NK cells. 30,38 In the current study, we found that NK cells downregulated their CD16 expression upon exposure to ovarian tumor microenvironment but this conversion was mitigated by PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The downregulation of CD16 on NK cells has been shown to be driven by TGFβ and leads to conversion from cytotoxic to a more immunoregulatory phenotype similar to decidual NK cells. 30,38 In the current study, we found that NK cells downregulated their CD16 expression upon exposure to ovarian tumor microenvironment but this conversion was mitigated by PD-L1 blockade. PD-L1 blockade also resulted in higher amounts of CD57 + NK cells, a subpopulation that have been reported to have a higher cytotoxic capacity with greater responsiveness via CD16 engagement and its presence correlated with better outcomes in squamous cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%